Boosting science mastery in rural classrooms: The power of the 5E inquiry model for secondary school students - Grace A. Bodiongan; Krizel Lourine B. Albezo; Merry Ann D. Pangasian (Eureka: Journal of Educational Research, 2026)
This action research examined the impact of inquiry-based learning (IBL) through the 5E (Engage, Explore, Explain, Elaborate, Evaluate) model on Grade 8 students' science achievement, with 42 students selected purposively from Laureano Salusod National High School (LSNHS), a government school in a remote area, Philippines, using a one-group pretest-posttest design. The 8-week intervention, using the 5E phases, targeted the fourth-quarter topics (Force, Motion, and Energy) in accordance with the MATATAG curriculum. It used a 40-item, teacher-made, validated test (Cronbach’s α=0.87) containing 20 conceptual, 10 problem-solving, and 10 application test items that assess performance in the following dimensions. For the quantitative results, mean percentage scores increased by 27.62 points from pretest (M=48.57; SD=9.23; Below Proficient) to posttest (M=76.19; SD=7.45; Proficient). The paired-samples t-test was statistically significant, t(41)=14.67, p-value<0.001, affirmed by the very large Cohen’s d effect size of 3.41. For the domains, application was highest at +31.4 points; problem-solving followed at +28.9 points; and conceptual was approximately +25.0 points. The reasoning showed the greatest improvement by honing the higher-order skills. In the features, the qualitative data showed that students were more engaged, more responsive, and more confident in conducting scientific inquiry, even though they were from a resource-limited school and had a language barrier. Therefore, the findings support the proposition of using localization and low-cost 5E-based IBL in improve science teaching and combat low performance in Philippine high schools with limited resources. Furthermore, the recommended action is the nationwide DepEd teacher training on IBL and its scaffolding strategies in multilingual forms.